2002
DOI: 10.1590/s0074-02762002000900026
|View full text |Cite
|
Sign up to set email alerts
|

Natural Schistosoma mansoni infection in Nectomys squamipes: histopathological and morphometric analysis in comparison to experimentally infected N. squamipes and C3H/He mice

Abstract: Histopathologic and morphometric (area, perimeter, major and minor diameters)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In the present study, naturally infected animals showed an immune response characterized by the strong presence of macrophages in the formation of different developmental stages of granulomas. The same finding was reported by Costa-Silva et al (2002), who studied N. squamipes naturally infected by S. mansoni. According to those authors, histopathological changes -both qualitative and quantitative -were less marked in naturally infected animals than in the experimental groups, suggesting that the intensity of the response to infection depends on the host species, the S. mansoni strain, and the number of cercariae.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, naturally infected animals showed an immune response characterized by the strong presence of macrophages in the formation of different developmental stages of granulomas. The same finding was reported by Costa-Silva et al (2002), who studied N. squamipes naturally infected by S. mansoni. According to those authors, histopathological changes -both qualitative and quantitative -were less marked in naturally infected animals than in the experimental groups, suggesting that the intensity of the response to infection depends on the host species, the S. mansoni strain, and the number of cercariae.…”
Section: Discussionsupporting
confidence: 87%
“…Reactions were classified as the pre-granulomatous stage (weakly reactive or nonreactive and exudative stages) or the granulomatous stage (exudative-productive, productive and involutional granulomas). The area, perimeter and major and minor diameter of individual granulomas were measured by computed image analysis (Image Pro-Plus Media Cybernetics, US), as described previously (Costa-Silva et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…granulomas was assessed and the granulomas were classified into three types (fibrous, cellular, and fibrocellular) according to the predominant component (Costa-Silva et al 2002). …”
Section: Article In Pressmentioning
confidence: 99%